Same-sex parenting according to the Italian Constitutional Court: the need for legislative solutions - Del Rio, Alessandro (Acta Biomedica Atenei Parmensis, 2022)
The authors have set out to analyze the most recent Italian Constitutional Court jurisprudence (rulings n. 32 and 33/2021) on the issue of surrogacy, by contextualizing the underlying factors and possible implications. The judges argue that their decisions are grounded in the best interest of the minor, whether born from surrogate motherhood or from heterologous fertilization, and believe that a legislative intervention to regulate the issue can no longer be postponed. According to that rationale, the legislator should take into account the difference between surrogacy and heterologous fertilization, and therefore the recognition of intentional parenthood cannot be unconditional, but must be differentiated, depending on the fertilization technique used.